Integrated motivational interviewing and cognitive behavioural therapy for people with psychosis and comorbid substance misuse: randomised controlled trial. (24th November 2010) - Barrowclough, Christine; Haddock, Gillian; Wykes, Til; Beardmore, Ruth; Conrod, Patricia; Craig, Tom; Davies, Linda; Dunn, Graham; Eisner, Emily; Lewis, Shôn; Moring, Jan; Steel, Craig; et al.
Abstract : Objectives To evaluate the effectiveness of integrated motivational interviewing and cognitive behavioural therapy in addition to standard care for patients with psychosis and a comorbid substance use problem. Design Two centre, open, rater blind randomised controlled trial. Setting Secondary care in the United Kingdom. Participants 327 patients with a clinical diagnosis of schizophrenia, schizophreniform disorder, or schizoaffective disorder and a diagnosis of dependence on or misuse of drugs, alcohol, or both according to the Diagnostic and Statistical Manual of Mental Disorders, fourth edition. Intervention The intervention was integrated motivational interviewing and cognitive behavioural therapy plus standard care, which was compared with standard care alone. Phase one of therapy—"motivation building"—concerns engaging the patient, then exploring and resolving ambivalence for change in substance use. Phase two—"action"—supports and facilitates change using cognitive behavioural approaches. Up to 26 therapy sessions were delivered over one year. Main outcome measures The primary outcome was death from any cause or admission to hospital in the 12 months after completion of therapy. Secondary outcomes were frequency and amount of substance use (assessed using the timeline followback method), readiness to change, perceived negative consequences of use, psychotic symptom ratings, number and duration of relapses, and global assessment of functioning and deliberate self harm at 12 and 24 months, with additional timeline followback assessments at 6 and 18 months. Analysis was by intention to treat and robust treatment effect estimates were produced. Results 327 participants were randomly allocated to either the intervention (n=164) or treatment as usual (n=163). At 24 months, 326 (99.7%) were assessed on the primary outcome and 246 (75.2%) on the main secondary outcomes. Treatment had no beneficial effect on hospital admissions or death during follow-up, with 23.3% (38/163) of the therapy group and 20.2% (33/163) of controls deceased or admitted (adjusted odds ratio 1.16, 95% confidence interval 0.68 to 1.99; P=0.579). Therapy had no effect on the frequency of substance use or the perceived negative consequences of misuse, but did have a statistically significant effect on amount used per substance using day (adjusted ORs for main substance 1.50, 95% CI 1.08 to 2.09; P=0.016; and all substances 1.48, 95% CI 1.07 to 2.05; P=0.017). Treatment had a statistically significant effect on readiness to change use at 12 months (adjusted OR 2.05, 95% CI 1.26 to 3.31; P=0.004) that was not maintained at 24 months (0.78, 95% CI 0.48 to 1.28; P=0.320). There were no effects of treatment on clinical outcomes such as relapses, psychotic symptoms, functioning, and self harm. Conclusions Integrated motivational interviewing and cognitive behavioural therapy for people with psychosis and substance misuse do not improve outcome in terms of hospitalisation, symptom outcomes, or functioning. This approach does reduce the amount of substance used for at least one year after completion of therapy. Trial registration Current Controlled Trials: ISRCTN14404480 .